Process innovation: enabling change by technology : basic principles and methodology : a management manual and textbook with exercises and review questions /: basic principles and methodology : a management manual and textbook with exercises and review questions. (2018) - Schallmo, Daniel R. A; Brecht, Leo; Ramosaj, Bujar
No abstract available